ASPEK HUKUM MEDIASI ATAS SENGKETA TANAH OLEH PIHAK BPN - IMMAN YUSUF SITINJAK (JURNAL ILMIAH MAKSITEK, 2019)
Land disputes are disputes arising from conflicts of interest in land. In principle, any land dispute can be resolved by existing norms and rules, or in other words, resolved based on applicable law. Basically, dispute resolution options can be made in 2 (two) processes. The process of resolving disputes through litigation in the court, then developing the process of dispute resolution through cooperation (cooperative) outside the court. The process of trying to resolve this dispute is usually called a family process. Mediation efforts by the BPN on land disputes are regulated in article 12 Paragraph 5 of Permen Number 11 of 2016 concerning Settlement of Land Cases: In the case of disputes or conflicts not the authority of the Ministry, the Ministry can take the initiative to facilitate the resolution of Disputes or Conflicts through Mediation. that the importance of the role of the BPN in striving to resolve land issues. This is because the BPN has more data and a basis for proof with the publication of data on land disputes. But the implementation of mediation needs legality. In this case questioning whether BPN has fulfilled the provisions in the implementation of mediation, namely the legal mediators. Because the provisions of the implementation of mediation must be referred to the provisions of PERMA 1 of 2016 concerning mediation procedures.